On the seismic behavior of masonry infilled frame structures - Dias-Oliveira, João (2022)
Infilled frames are usually modelled in the context of global building analysis using simplified procedures without considering the aspects resulting from the interaction between the panel and the frame. Other aspects, such as adequate design of the floor beams and the beam-columns’ joints, and control of potential sliding shear failure of the columns, that significantly affect the structural response, are also typically not accounted for. In the present work it is intended to look over the literature to evaluate the state of the art regarding the lessons learn from recent earthquakes, the evolution of the structural codes considering the infill masonry panels, and how this influences the evolution of the numerical models and the experimental works to overcome the existent gaps.